2021
DOI: 10.3390/ijms222212196
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Amphidinol Profiling of the Marine Dinoflagellate Amphidinium carterae (Subclade III)

Abstract: Microalgae have received growing interest for their capacity to produce bioactive metabolites. This study aimed at characterising the antimicrobial potential of the marine dinoflagellate Amphidinium carterae strain LACW11, isolated from the west of Ireland. Amphidinolides have been identified as cytotoxic polyoxygenated polyketides produced by several Amphidinium species. Phylogenetic inference assigned our strain to Amphidinium carterae subclade III, along with isolates interspersed in different geographic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Many bioactive and pharmacologically active chemicals, particularly antibacterial compounds, are potentially produced by marine microalgae [6,20,21]. Furthermore, microalgae are gaining popularity due to their ability to create bioactive metabolites with anticancer, anti-inflammatory, antibacterial, and antioxidant effects [11,22]. Previous studies have suggested that fatty acids [23], terpenoids, carbohydrates [24], peptides, polysaccharides, and alkaloids are responsible for antibacterial activity in microalgae [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many bioactive and pharmacologically active chemicals, particularly antibacterial compounds, are potentially produced by marine microalgae [6,20,21]. Furthermore, microalgae are gaining popularity due to their ability to create bioactive metabolites with anticancer, anti-inflammatory, antibacterial, and antioxidant effects [11,22]. Previous studies have suggested that fatty acids [23], terpenoids, carbohydrates [24], peptides, polysaccharides, and alkaloids are responsible for antibacterial activity in microalgae [25].…”
Section: Discussionmentioning
confidence: 99%
“…Novel antibacterial substances were also discovered in microalgae, with Coccomyxa onubensis fatty acid extracts inhibiting E.coli and P. mirabilis [26]. Furthermore, microalgae have been increasingly treated with other compounds such as cyanovirin, oleic acid, linoleic acid, palmitoleic acid, -carotene, or phycocyanin, which have antioxidant or anti-inflammatory properties, as well as antimicrobial activity, such as against Staphylococcus aureus and methicillin-resistant Staphylococcus aureus (MRSA) [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…340 Other compounds were claimed but were only established by MS-methods and their structures are not shown here. [341][342][343] The total synthesis of limaol has been achieved, 344 while the relative and absolute congurations of formosalide A 884 and B 885 have been established following their syntheses. 345 Two groups have independently synthesised and determined the full stereostructure of amphirionin-2 886.…”
Section: Dinoagellatesmentioning
confidence: 99%
“…Other compounds were claimed but were only established by MS-methods and their structures are not shown here. 341–343…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…In some of these events, Amphidinium bHABs have been related to fish kills, with A. carterae , A. gibossum , A. massartii, and A. operculatum reported as ichthyotoxin producers [ 5 , 6 , 8 , 9 , 10 , 11 ]. However, besides fish toxicity, some polyketides produced by Amphidinium species have been shown to possess potentially useful bioactivities, such as antifungal, cytotoxic, and antimicrobial bioactivities [ 12 , 13 , 14 ]. Yet, only some of the members of the genus or the species, and not even all members of the same strain, can synthesize these polyketides [ 15 ].…”
Section: Introductionmentioning
confidence: 99%